A multi-biomarker analysis of the antioxidant efficacy of Parkinson's disease therapy. (March 2018) - Colamartino, Monica; Duranti, Guglielmo; Ceci, Roberta; Sabatini, Stefania; Testa, Antonella; Cozzi, Renata
Abstract: Substantial evidences suggest that reactive oxygen species participate in the normal aging process and in cancer and neurodegenerative age-related diseases. Parkinson's disease (PD), one of the most common oxidative stress-associated pathology in aging people, is treated with a standard pharmacological protocol consisting in a combined therapyl -dopa plus an inhibitor of dopa-decarboxylase, such as carbidopa. The therapy is well validated for the ability to restoring dopaminergic neurotransmission in PD patients, whilel -dopa and carbidopa ability in modulating oxidative stress is currently under discussion. Our aim was to evaluate the impact ofl -dopa and carbidopa on several biomarkers of exogenously-induced oxidative stress to validate the overall antioxidant effectiveness of the therapy. For this purpose we used peripheral blood lymphocytes from healthy donors treated in vitro withl -dopa and carbidopa and then challenged by different concentrations of H2 O2 . Glutathione (GSH, GSSG, GSH/GSSG), malondialdehyde (TBARs), protein carbonyls as well as DNA damage (8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodG) and micronuclei (MN)), modulation was evaluated. Our results show thatl -dopa, but not carbidopa, decreases the markers of lipid and protein oxidation and increases the total content of glutathione. Bothl -dopa and carbidopa (alone or in combination) are able to counteract the formation of 8-oxodG and to reduce H2 O2 -induced micronuclei. Highlights: l -Dopa and carbidopa per se do not induce oxidative stress. Both molecules are able to reduce DNA and chromosome damage induced by H2 O2 . The combined effectl -dopa + carbidopa is more efficient in reducing 8-oxo-dG levels. l -Dopa in single and combined treatments restores the redox status of cells and reduces lipid and protein oxidation.